Diversifying Urban Gardens in Quezon City, Philippines, with Climate-Resilient Nutrient-Dense Vegetables - Kimayong, Doreen; Anunciado, Ma. Shiela S.; Gonsalves, Julian; Oro, Emilita Monville; De Castro, Ronnie; Schreinemachers, Pepijn; Bertuso, Arma (CGIAR Initiative on Resilient Cities, 2024)
Sustainable food production is essential for meeting the needs of a growing global population and increasing urbanization. By 2050, 60% of people will live in urban areas, with over 3 billion in cities (FAO 2015). Urbanization presents challenges such as limited land availability, high costs of resources, and environmental issues like soil contamination, pollution, and climate change. In response, urban agriculture has gained global attention as a way to produce local fresh food and promote sustainable cities (Dumat et al. 2016). Quezon City, a highly urbanized area in Metro Manila, has adopted urban agriculture to boost food security, enhance nutrition, and promote sustainable practices. The Joy of Urban Farming (JOUF) Program has been instrumental in establishing community gardens to increase the availability and accessibility of vegetables for urban households. Complementing this effort, the CGIAR Resilient Cities Initiative, under Work Package 1 on Sustainable Food Production, focuses on improving urban and peri-urban food systems by introducing advanced technologies, practices, and services for cleaner and safer food production